Título de pago diferido: un instrumento de financiación para inclusión de pymes en el esquema de segundo mercado en Colombia - Carvajal Herrera, Luz Helena; Barragán Arias, Isabel C.; Quiñónez Avendaño, Camilo (Libre Empresa, 2017)
The SMEs in Colombia are an economic engine and provide the 76% of employment (Supersociedades, Abril 2012). For to achieve growth and continuity they come to the financial system looking financial resources, with limited policies of credit risk for this target, with restrictive in amount and term; further the providers go on presents like a financial leverage working capital, with an implicit financial that impact on the profit margin and financial structure. The Colombian Ministry of Treasury and public credit, with the decrees 2555/2010 and 1019/2014 promotes the second market, an alternative in the inclusion of issuers to stock market and the opportunity to propose the “ Title Deferred Payment - TDP”, an instrument of leverage short term.